Impact 0f Prosecution Against Infringement Ticketing with Numbers Traffic Accidents in The Jurisdiction of Police Resort Semarang - Rudi Hendri Basuki; Umar Ma’ruf (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This study aims to determine how is the implementation of the action by infringing traffic by a speeding ticket in the jurisdiction of Police in Semarang; How can the impact of infringing on a traffic enforcement with a ticket to the number of traffic accidents in the jurisdiction of Police in Semarang; and What constraints in action by infringing traffic by a speeding ticket in the jurisdiction of Semarang Police and how the solutions to overcome them.The method used by the author in this study is juridical empirical or sociological jurisdiction. Specifications of research used is descriptive analyticalBased on research conducted can be concluded that 1) Implementation of Traffic Violations Enforcement accordance with Government Regulation on Infringement Ticketing Act No. 80 Of 2012 on Procedures for Vehicle Inspection and Enforcement Violations On the Road Traffic and Transportation Article 3, which reads Vehicle Inspection; 2) The results in January to September 2018 is known that the impact of a speeding ticket to a very significant definitely one transport accident means the higher the number the lower the accident rate speeding ticket, speeding ticket conversely the lower the number the higher the number of accidents; and 3) Constraints in the prosecution of traffic violations by a speeding ticket in the jurisdiction of Semarang Police isThe lack of legal awareness in the society, lack of ability by the Police Authority problematic legislation, the lack of infrastructure to supportKeywords: Impact; Infringement; Traffic; Infringement Ticketing; Accident.